2015
DOI: 10.1097/md.0000000000001707
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Serum IgG4 Levels in Patients With IgG4-Related Disease

Abstract: The aim of this study is to study the clinical features and diagnostic performance of IgG4 in Chinese populations with IgG4-related diseases (IgG4-RDs).The medical records of 2901 adult subjects who underwent serum IgG4 level tests conducted between December 2007 and May 2014 were reviewed.Serum concentrations of IgG4 were measured in 2901 cases, including 161 (5.6%) patients with IgG4-RD and 2740 (94.4%) patients without IgG4-RD (non-IgG4-RD group). The mean age of the IgG4-RD patients was 58.4 ± 16.1 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 54 publications
4
39
0
3
Order By: Relevance
“…In our case, repeated measures of serum IgG4 level showed a largest value of four times the upper limit of normal. Although the upper limit of the serum IgG4 level was rather different from that in Yu et al study, an IgG4 level of 427 mg/dL was greater than the 405 mg/dl cutoff value cited in the study by Yu et al where a sensitivity, specificity, positive predictive value, and negative predictive value were 62, 98, 68, and 98 %, respectively [37]. We excluded the possibility of malignant lymphoma or other malignant tumors using PET/CT, gallium scintigraphy, and whole-body CT, as well as soluble IL2R measurement.…”
Section: Lack Of Histology and Differential Diagnosismentioning
confidence: 68%
See 1 more Smart Citation
“…In our case, repeated measures of serum IgG4 level showed a largest value of four times the upper limit of normal. Although the upper limit of the serum IgG4 level was rather different from that in Yu et al study, an IgG4 level of 427 mg/dL was greater than the 405 mg/dl cutoff value cited in the study by Yu et al where a sensitivity, specificity, positive predictive value, and negative predictive value were 62, 98, 68, and 98 %, respectively [37]. We excluded the possibility of malignant lymphoma or other malignant tumors using PET/CT, gallium scintigraphy, and whole-body CT, as well as soluble IL2R measurement.…”
Section: Lack Of Histology and Differential Diagnosismentioning
confidence: 68%
“…Thus, the diagnosis of suspected IgG4-RD was limited to a possibility at best, and was performed by checking for elevated levels of serum IgG4 and the presence of multiple periarterial lesions, as indicated in the comprehensive clinical diagnostic criteria for IgG4-RD [16,36]. Recently, Yu et al reported that a level of two or three times the upper limit of the manufacturer's reference range for serum IgG4 is a marker of various types of IgG4-RD [37]. The optimal cutoff value of serum IgG4 for the diagnosis of IgG4-RD was 248 mg/day, and the sensitivity and specificity were 77.6 and 92.8 %, respectively.…”
Section: Lack Of Histology and Differential Diagnosismentioning
confidence: 98%
“…3,21,[61][62][63] Serum IgG4 level has been reported to be elevated in 50% to 95% of patients with active IgG4-RD. 8,61,63,64 Conversely, only 10% to 20% of patients with an elevated serum IgG4 level in clinical practice have IgG4-RD. 62,65,66 Thus, an elevated serum IgG4 level is supportive of the diagnosis of IgG4-RD but not necessary nor sufficient.…”
Section: Serum Immunoglobulin G4 Levelmentioning
confidence: 91%
“…Additional IgG4-RDs have been identified, based on systemic fibroinflammatory disease characterized by the presence of lesions with lymphoplasmacytic infiltrate with high levels of IgG4-positive plasma cells. In addition,a correlation between higher levels of IgG4 and good response to therapy with corticoids has been observed [2,[6][7][8][9][11][12][13][14][15][16][17][18]. Hamano et al, [19,20] observed not only elevated levels of IgG4 in autoimmune pancreatitis, but also found characteristic histopathological manifestations accompanying retroperitoneal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Polyclonal increase of IgG4 levels as a result of common food and animal-derived allergens supports the idea of potential damage of regulatory mechanisms of immune system [33]. It is important to note that IgG4-RD can be diagnosed even without elevated levels of IgG4 [18,34]. Despite clear progress, dependable diagnostic criteria remain to be found [21,22].…”
Section: Review Diagnosismentioning
confidence: 99%